Optimization of a flexible manufacturing system (FMS) for high technology product producing factory via the modularization of production systems - Karunakaran, P.; Osman, M.S (IJMERR, 2012)
This research is timely because many High Technology Product Producing Factories (HTPPF) are still following the trend of factories that produces the likes of canned food or even cars where all machines are jointed from start to end (Towill, 2010). These HTPPF have not realized that improvements to product must be done everyday to keep market share. And to perform research continuously, buffers in-between production machines is a necessity. The absence of this has caused a number of hard disk manufacturers to close down, especially in Japan and Taiwan (notably Sony, NEC, Matsushita and Trace), which are leaders in joining up production lines from start to end. It is due to this that currently 90% of hard disks are produced by Western Digital and Seagate, with Toshiba having 10% market share.